Informal caring and labour market outcomes within England and Wales - Stephen Drinkwater (Institute for the Study of Labor (IZA), 2011)
This paper focuses on the links between informal care provision and labour market activity at the sub-national level. Within-country analysis of this issue has been very limited to date despite the wide regional variations in informal care provision that often exist. This issue is important in the context of policy decisions in Wales and other parts of the UK because of relatively high levels of informal caring in certain areas, especially in the South Wales Valleys. In particular, given that these areas typically have the lowest economic activity and employment rates, labour market differences can be exacerbated by the provision of informal caring by people of working age. Despite the wide variations in informal care provision, it is found that labour market outcomes do not differ markedly by different care categories across spatial areas within England and Wales. However, the analysis reveals that labour market outcomes for males as well as females are heavily influenced for those who provide high levels of caring, especially in the South Wales Valleys. For example, the largest impact of caring on the probability of not working for males and for part-time work for females is seen in this area.
urn:nbn:de:101:1-201108093041
Keywords: J22; R23; 330; informal care provision; labour market outcomes; area variations